Dual-input DC-DC Buck Converter using Fuel Cell and Battery Source - Mohd Sepawi, Fairuz Nadhirah; Utomo, Wahyu Mulyo (Evolution in Electrical and Electronic Engineering, 2021)
The integration of various energy sources to efficiently utilise renewable energy is a current trend in the power system. The development of a power electronic interface is very significant for the successful integration of those sources. In this paper, a dual-input dc-dc buck converter is designed and simulated for load supply using MATLAB Simulink software. The dual-input dc-dc converter can work with two different sources. The use of Fuel Cell (FC) and battery sources is an alternative way to get a larger output power value for the load supply. The simulation results show that the dual-input dc-dc buck converter can work in a state-supplied by two different sources and show better output performances than a single-input dc-dc converter with an output power of 107.5 W.